Neurophysiology versus clinical genetics in Rett syndrome: A multicenter study. Issue 9 (29th June 2016) - Halbach, Nicky; Smeets, Eric E.; Julu, Peter; Witt‐Engerström, Ingegerd; Pini, Giorgio; Bigoni, Stefania; Hansen, Stig; Apartopoulos, Flora; Delamont, Robert; van Roozendaal, Kees; Scusa, Maria F.; Borelli, Paolo; et al.
Abstract : Many studies have attempted to establish the genotype–phenotype correlation in Rett syndrome (RTT). Cardiorespiratory measurements provide robust objective data, to correlate with each of the different clinical phenotypes. It has important implications for the management and treatment of this syndrome. The aim of this study was to correlate the genotype with the quantitative cardiorespiratory data obtained by neurophysiological measurement combined with a clinical severity score. This international multicenter study was conducted in four European countries from 1999 to 2012. The study cohort consisted of a group of 132 well‐defined RTT females aged between 2 and 43 years with extended clinical, molecular, and neurophysiological assessments. Diagnosis of RTT was based on the consensus criteria for RTT and molecular confirmation. Genotype–phenotype analyses of clinical features and cardiorespiratory data were performed after grouping mutations by the same type and localization or having the same putative biological effect on the MeCP2 protein, and subsequently on eight single recurrent mutations. A less severe phenotype was seen in females with CTS, p.R133C, and p.R294X mutations. Autonomic disturbances were present in all females, and not restricted to nor influenced by one specific group or any single recurrent mutation. The objective information from non‐invasive neurophysiological evaluation of the disturbed central autonomic control is of great importance in helping to organize the lifelong care for females with RTT. Further research is needed to provide insights into the pathogenesis of autonomic dysfunction, and to develop evidence‐based management in RTT. © 2016 Wiley Periodicals, Inc.